2008
DOI: 10.1158/1078-0432.ccr-07-4521
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Gemcitabine in Patients with Refractory Tumors: A Clinical and Pharmacologic Study

Abstract: Purpose: To determine the toxicity, tolerability, pharmacokinetics, pharmacodynamics, and preliminary antitumor activity of oral gemcitabine (2 ¶,2 ¶-difluorodeoxycytidine; dFdC) in patients with cancer. Experimental Design: Patients with advanced or metastatic cancer refractory to standard therapy were eligible. Gemcitabine was administered p.o. starting at 1 mg once daily using dose escalation with three patients per dose level. Patients received one of two dosing schemes: (a) once daily dosing for 14 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…The slope of the initial linear formation rate was used to determine the Cl int since there was a linear relationship between dFdUMP formation by DCK and dFdU concentration. The high dFdUMP concentrations previously reported (Veltkamp et al, 2008) either were formed through direct phosphorylation of dFdU by another kinase, or resulted from the biotransformation of dFdCMP to dFdUMP by deoxycytidine monophosphate deaminase (Mini et al, 2006). As a result, no further studies were conducted on the effects of other DCK variants in the conversion from dFdU to dFdUMP.…”
Section: Downloaded Frommentioning
confidence: 96%
See 1 more Smart Citation
“…The slope of the initial linear formation rate was used to determine the Cl int since there was a linear relationship between dFdUMP formation by DCK and dFdU concentration. The high dFdUMP concentrations previously reported (Veltkamp et al, 2008) either were formed through direct phosphorylation of dFdU by another kinase, or resulted from the biotransformation of dFdCMP to dFdUMP by deoxycytidine monophosphate deaminase (Mini et al, 2006). As a result, no further studies were conducted on the effects of other DCK variants in the conversion from dFdU to dFdUMP.…”
Section: Downloaded Frommentioning
confidence: 96%
“…Cells lacking DCK activity are resistant to the dFdC cytotoxicity (Mini et al, 2006). Additionally, dFdU was reported to form dFdU monophosphate (dFdUMP) via direct phosphorylation (Veltkamp et al, 2008), but it is unknown whether DCK is involved (Supplemental Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration would permit gemcitabine to be given on a more frequent basis that may further enhance efficacy. Clinical studies of the oral availability of gemcitabine found low systemic exposure due to rapid first pass metabolism to dFdU and gastrointestinal toxicity (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, daily and every other day oral administration of gemcitabine was studied in a previous clinical trial (12). The pharmacokinetic data obtained in this trial revealed that this approach was not feasible because of lack of bioavailability.…”
Section: Introductionmentioning
confidence: 99%